Dynamic compression properties of microcapsule-fiber cementitious composites - WANG Xianfeng; SHENG Min; QIN Dawei; ZHOU Xiaoqing; XING Feng (Shenzhen Daxue xuebao. Ligong ban)
The microcapsule-based self-healing cementitious materials have good repaire performance. However, the mechanical performance is weakened due to the introduction of microcapsules. The addition of fibers can improve the cracking performance and form an effective complement to the microcapsules. In order to study the influence of fiber type and strain rate on the compressive properties of microcapsule self-healing cement-based materials , we design three strain rate loading tests are on experimental specimens of three mix proportion types, namely polyvinyl alcohol (PVA) fibers, polyamide (PA) fibers and PVA-PA hybrid fibers through the cube compression test and the split Hopkinson pressure bar (SHPB) test. The results show that when the strain rate is 10-5 s-1, the compressive strength of self-healing cement-based materials decreases by 12.96%, 8.91% and 9.03% after adding PVA, PA and PVA-PA, respectively. With the increase of the strain rate, the compressive strength of the material increases, and the dynamic growth factor of the material has a linear relationship with the strain rate. At low strain rate, fibers can improve the energy absorption capacity of the material. The dissipated energy and energy dissipation factor are improved. This study could provide experimental basis for improving self-healing performance of concrete materials under dynamic conditions.